2021
DOI: 10.1016/j.ijid.2020.12.066
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of pediatric febrile urinary tract infection in Japan

Abstract: Background: Febrile urinary tract infection (fUTI) is the most common serious bacterial infection in children. Despite this, there have been no studies examining the clinical features of pediatric fUTI in Japan. The purpose of this study was to describe the clinical characteristics of fUTI in Japanese children. Methods: A multicenter, retrospective, observational study was conducted at 21 hospitals in Japan. Children under the age of 15 years who were diagnosed with fUTI between 2008 and 2017 were included. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…Common uropathogens include Escherichia coli (accounting for more than 80% organisms causing UTIs in children), Klebsiella, Proteus, Enterobacter, Enterococcus, Citrobacter, and Staphylococcus saprophyticus (adolescent girls) [28,29]. In a Japanese retrospective study, the febrile UTIs caused by Enterococcus showed a more marked male predominance compared with E. coli, a higher prevalence of VUR, and more frequent recent antibiotic use [30]. It was reported that UTIs caused by enterococcus was associated with more underlying urinary tract anomalies than gram-negative UTI and more inappropriate antibiotic therapy, which need adequate imaging and antibiotic therapy [31].…”
Section: Common Uropathogensmentioning
confidence: 99%
See 1 more Smart Citation
“…Common uropathogens include Escherichia coli (accounting for more than 80% organisms causing UTIs in children), Klebsiella, Proteus, Enterobacter, Enterococcus, Citrobacter, and Staphylococcus saprophyticus (adolescent girls) [28,29]. In a Japanese retrospective study, the febrile UTIs caused by Enterococcus showed a more marked male predominance compared with E. coli, a higher prevalence of VUR, and more frequent recent antibiotic use [30]. It was reported that UTIs caused by enterococcus was associated with more underlying urinary tract anomalies than gram-negative UTI and more inappropriate antibiotic therapy, which need adequate imaging and antibiotic therapy [31].…”
Section: Common Uropathogensmentioning
confidence: 99%
“…RBUS serves as an ideal tool for initial screening for anatomic abnormalities in infants with UTI because of its noninvasive nature, lack of radiation, good anatomic demonstration of the entire urinary system, and low cost. Though two Japanese studies suggested that around 50% of pediatric UTI patients who show no signs of abnormalities using RBUS, nevertheless those children had a high-grade VUR [30,53]. Ultrasound scanning is a good tool to assess obstructive uropathies, urolithiasis, ectopic kidney or ureter, posterior urethral valves, and duplication of the collecting system with or without ureterocele.…”
Section: Imaging Toolsmentioning
confidence: 99%
“…Educational system involving microbiologists has been established in some teaching hospitals. Gram staining is useful for selecting antibiotics if used wisely 5 ; however, we…”
Section: Descriptionmentioning
confidence: 96%
“…5 Furthermore, fUTI by bacteria other than Escherichia coli is more frequently associated with urinary tract abnormalities than E. coli-induced fUTI. 7,8 Unlike E. coli, no constant virulence factors other than endotoxins found in Klebsiella or Enterobacter species, which are less likely to cause infection in patients without urinary tract abnormalities. 9 Thus, children with non-E. coli-induced fUTI are recommended to undergo VCUG.…”
Section: Introductionmentioning
confidence: 99%
“…In this setting, the indication for implementing VCUG for early childhood with E. coli-induced fUTI depends on the disease severity and the results of non-invasive imaging studies, including RBUS, which have poor sensitivity in the detection of VUR. 8,10 In our hospital, VCUG has been performed for all patients with their first fUTI until 2014, when the AAP guidelines were launched based on the results of previous studies. 5,7,8,11,12 Thereafter, VCUG has been implemented for those with abnormal RBUS findings, complications of bacteremia, acute focal bacterial nephritis (AFBN) or non-E. coli-induced fUTI.…”
Section: Introductionmentioning
confidence: 99%